2018
DOI: 10.14260/jemds/2018/527
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Haematological and Biochemical Profile of Dimorphic Anaemia With Bone Marrow Study

Abstract: BACKGROUND Dimorphic anaemia is very common in India. Dimorphism indicates the presence of two distinct populations of red cells. The term is most often applied when there is one population of hypochromic, microcytic cells and another population of normochromic cells, either normocytic or macrocytic. Aims and Objectives-1. Dimorphic anaemia has been studied, because treatment may be ineffective if the dual deficiency is not diagnosed. 2. To correlate and compare the clinico-haematological, biochemical paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
2
0
0
Order By: Relevance
“…Pallor was present in all the patients in our study, and this was comparable to the survey by Gayathri BN et al [23], Rathwa SS et al [24]. In present study splenomegaly was seen in 40.2% cases, accordance with the Rawat S, et al [25], observed splenomegaly in 35.3% of megaloblastic anaemia cases. In this study, observed the common clinical signs were pallor, glossitis, edema, jaundice, hepatomegaly, splenomegaly and hyper pigmentation, comparable with the Deepankar P, et al [26], B.R.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Pallor was present in all the patients in our study, and this was comparable to the survey by Gayathri BN et al [23], Rathwa SS et al [24]. In present study splenomegaly was seen in 40.2% cases, accordance with the Rawat S, et al [25], observed splenomegaly in 35.3% of megaloblastic anaemia cases. In this study, observed the common clinical signs were pallor, glossitis, edema, jaundice, hepatomegaly, splenomegaly and hyper pigmentation, comparable with the Deepankar P, et al [26], B.R.…”
Section: Discussionsupporting
confidence: 92%
“…Folate deficiency is also another important cause of megaloblastic anemia. In this study, the most common age of presentation of megaloblastic anemia was in the subjects aged 16-30 years, our finding was comparable with the Kaur et al [10] and Khanduri et al [11], which suggest that MA is more prevalent in young age Present study observed slight male predominance (56.1%) over the female (43.9%) of the megaloblastic anaemia patients, Our result was similar to Ratre BK, et al [12], Rawat S et al [13] and Gupta M et al [14] In present study most of the (54.5%) megaloblastic anemia patients were moderate in nature (Hb 7-10%), our finding was concordance with the Choudhary P et al [15] and Mishra R et al [16] Current study observed megaloblastic anaemia was higher among pure vegetarian persons, similar finding also found by Gupta RK et al [17] and KK Magnani, et al [18].…”
Section: Discussionsupporting
confidence: 90%